Analisis Fonologis terhadap Pengucapan Bahasa Indonesia oleh SunnyDahye, Selebgram Korea di Platform TikTok - Devi Ayu Rizkiyanda; Jenia Evelin Luthfianingtyas; Elok Triana Azzahra Luckys; Shofia Nailal Hidayah; Luthfa Nugraheni (BLAZE : Jurnal Bahasa dan Sastra dalam Pendidikan Linguistik dan Pengembangan, 2025)
The growth of digital technology and social media platforms has promoted intercultural communication, especially in second language acquisition by non-native speakers. This study examines phonological deviations in the Indonesian pronunciation of SunnyDahye, a South Korean influencer who frequently uses the language in her TikTok content. Employing a descriptive qualitative approach, data were collected from five purposively selected videos based on the clarity of audio and frequency of Indonesian usage. The analysis focused on segmental (consonants and vowels) and suprasegmental (intonation and stress) features using the International Phonetic Alphabet (IPA). Findings reveal notable instances of phonological interference, including the substitution of the alveolar trill /r/ with /l/, mispronunciations of the schwa vowel /ə/ replaced with /e/ or /a/, and flat intonation patterns influenced by Korean prosody. These deviations are rooted in the phonological system of the Korean language, which lacks certain Indonesian phonemes and prosodic features. The results emphasize the influence of first language phonology on second language articulation and underscore the importance of incorporating contrastive phonetic analysis in Bahasa Indonesia instruction for foreign learners. The study contributes to broader discussions in applied linguistics and second language pedagogy, particularly for the Indonesian for Foreign Speakers (BIPA) program.